Exercise programme for schoolgirl with poor posture - Bendíková, Elena; Görner, Karol; Paugshová, Božena (Journal of Education, Health and Sport, 2016)
Abstract The pilot study explains how important it is to include the intervention exercise programme in the syllabi of physical and sport education, especially in terms of primary prevention and improvement of dynamic postural stereotype of pupils. The experimental group consisted of nine female pupils who attended one elementary school in the town of Liptovský Mikuláš and whose age was 13.6 years. We obtained data using the standardized method based on pedagogical and medical practice connected with evaluation of body posture. We used the Wilcoxon signed-rank test to process the obtained qualitative and quantitative data within individual groups. The Wilcoxon-Mann–Whitney test was used to assess the effect of exercise programmes between the two groups (MWWtest p < 0.01; p < 0.05). The test results proved the positive impact of the applied exercise programme on overall posture as well as its individual components. The partial output is part of the: VEGA 1/0376/14.